Isolation and characterization of EBR specific induced chitinases from tobacco (Nicotiana tabacum) - Szabó, Erika (Acta Biologica Szegediensis, 2008)
Early basal resistance (EBR) is a quick resistant response for pathogenic attack. Apoplastic proteins in plant intercellular space may play important role in triggering this response. Two chitinase enzyme –which’s appearance is strongly connected to the early stage of this process - were isolated on HIC and further analysed. N-terminal aminoacid sequence were determined and their identification as IV class chitinases was proved. Our aim is to widen our knowledge about the expression, regulation of these enzymes. Also to analyse their role in the pathway leading from pathogen perception to resistance appearance.